2021
DOI: 10.3389/fcell.2021.756458
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Inflammatory Signaling and Methylation in Cancer

Abstract: Inflammation is an intricate immune response against infection and tissue damage. While the initial immune response is important for preventing tumorigenesis, chronic inflammation is implicated in cancer pathogenesis. It has been linked to various stages of tumor development including transformation, proliferation, angiogenesis, and metastasis. Immune cells, through the production of inflammatory mediators such as cytokines, chemokines, transforming growth factors, and adhesion molecules contribute to the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 192 publications
(214 reference statements)
0
4
0
Order By: Relevance
“…Aside from these two histone modifications, histone phosphorylation and ubiquitination have also gradually gained attention for their crucial roles in regulating transcription and chromatin structure. As the roles of histone and DNA methylation/demethylation in cancer and inflammation have been recently and extensively reviewed ( Das et al, 2021 ), here we focus on the mechanistic basis of histone acetylation/deacetylation, phosphorylation and ubiquitination, and how they mediate inflammatory signaling in cancer.…”
Section: Chromatin Modificationsmentioning
confidence: 99%
“…Aside from these two histone modifications, histone phosphorylation and ubiquitination have also gradually gained attention for their crucial roles in regulating transcription and chromatin structure. As the roles of histone and DNA methylation/demethylation in cancer and inflammation have been recently and extensively reviewed ( Das et al, 2021 ), here we focus on the mechanistic basis of histone acetylation/deacetylation, phosphorylation and ubiquitination, and how they mediate inflammatory signaling in cancer.…”
Section: Chromatin Modificationsmentioning
confidence: 99%
“…JMJD3 is involved in the regulation of macrophage polarization, with its expression are higher in M1‐polarized macrophages compared to M2‐polarized macrophages. [ 106 ] HDAC3 controls the regulation of inflammatory genes in macrophages, while histone deacetylase 2 (HDAC2) contributes to the resolution of inflammation. [ 107 ] In monocytes isolated from T1DM and T2DM patients, acetylation of H3 at the promoter of TNF and COX2 genes was increased, whereas H3K4 mono‐methylation contributes to monocyte dysfunction in T2DM patients by inducing transcription of NF‐kBp65 and proinflammatory genes like VCAM‐1, ICAM‐1, and MCP‐1.…”
Section: The Interplay Between Epigenetics and Immunometabolic Disordersmentioning
confidence: 99%
“…Transmembrane protein 178 (TMEM178, also known as TMEM178A), a member of the TMEM family, is located on chromosome 2p22.1. Previous studies showed the production and accumulation of pro-inflammatory cytokines, and the imbalance of calcium level are important factors to stimulate the progress of cancer ( 5 , 6 ). TMEM178 reduced the STIM1 puncta formation and the production of inflammatory cytokines IL-6, IL-1 β and TNF α, resulting in impairment of inflammatory response in cancer ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%